Perlindungan Pelaku Usaha Atas Review Food vlogger Perspektif Wahbah Az-Zuhaili: Studi Kasus di platfrorm Tik Tok - Erlina Sari Hasibuan,; Rahmat Hidayat, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research discusses the protection of business actors regarding Food vlogger reviews on TikTok with a focus on Wahbah Az-Zuhaili's perspective. In this case, food vloggers review the quality of restaurant food and service and upload them to social media without the business owner's knowledge. The content published by food vloggers received responses from various viewers, both positive and negative. When reviews are negative, it causes a decrease in customers which ultimately harms business actors. Food vlogger reviews have an impact on reducing customers which results in less income for business actors. This research uses empirical juridical methods by collecting data from literature searches. From this research, it was found that food vlogger reviews have an impact on sales, but what needs to be paid attention to is that the reviews given by food vloggers should use polite language and still provide suggestions so that business actors know what to improve. As explained by Wahbah Az-Zuhaili, this impact can be an opportunity and challenge for the culinary business. A social media user must be smart in choosing diction and speak in moderation. Words that contain encouragement or motivation and don't speak if only to offend other people's feelings. Because indeed Allah SWT hates people who exaggerate in anything.